Understanding consumer behavior in Lebanon’s polycrisis: The role of ethnocentrism, coping ability, and socioeconomic status - Imad Bou-Hamad (PLoS ONE, 2026)
Consumer behavior during crisis has grown into an increasingly significant subject of study, as financial and social disturbances affect purchase choices and market dynamics. In Lebanon, a country experiencing a prolonged economic crisis and societal instability, businesses and policymakers face urgent challenges in maintaining consumer demand for domestic products. Drawing on the Theory of Reasoned Action and the Transactional Model of Stress and Coping, this study aims to investigate the demographic, psychological, and socioeconomic predictors of ethnocentrism and purchasing intentions for Lebanese products in this environment. A quantitative approach was adopted. Data were collected from 606 Lebanese consumers through a structured survey between March and May 2021 during the country’s financial collapse, COVID-19 pandemic, and Beirut port explosion. The findings show that ethnocentrism (β = 0.253, p < 0.001) and SES (β = 1.479, p = 0.003) directly predict purchase intentions for Lebanese products. Demographic factors influence ethnocentric tendencies, and coping ability operates more strongly among older consumers (β = −0.023, p = 0.047). Ethnocentrism partially mediates the age effect, while SES shows inconsistent mediation patterns. These insights extend psychological models of behavior by demonstrating how coping mechanisms and socioeconomic standing interact with identity-based attitudes to influence consumption during national crises. The study offers theoretical contributions relevant to crisis contexts and provides practical insights for marketers and policymakers aiming to strengthen domestic markets through targeted segmentation and culturally aligned messaging.